Efektifitas Perbandingan Buerger Allen Exercise dan Senam Kaki terhadap Nilai ABI pada Penderita DM Tipe II - Awinda Sari; Anwar Wardy W; Yani Sofiani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study is to obtain a comparison of the effectiveness of the Buerger Allen Exercise and foot exercises on the value of the Ankle Brachial Index (ABI) in patients with Type II Diabetes Mellitus. This research method is a quantitative method with a research design Quasi Experiment pre and post test two groups. The results showed that there was a significant difference in the value of the Ankle Brachial Index (ABI) before and after being given Buerger Allen Exercise and foot exercises, namely p <0.05 with the difference in the average difference in the increase in ABI values in the Buerger Allen Exercise group of 0.0820, while in the leg exercise group, the difference in the average increase in the ABI value was 0.0726. In conclusion, Buerger Allen exercise is more effective than leg exercises in increasing the value of the Ankle Brachial Index (ABI). Keywords: Ankle Brachial Index, Buerger Allen Exercise, Type II Diabetes Mellitus, Foot Exercise